Keterlibatan Kerja pada Anggota Kepolisian: Tinjauan Sistematis terhadap Faktor-faktor yang Meningkatkan Keterlibatan Kerja - Agustina Inesia; Bonita Sandika; Eka Putri; Phyu Sin Yadanar Thein (Cerdika: Jurnal Ilmiah Indonesia, 2024)
Work involvement is an important phenomenon in the context of organizations, especially in demanding environments such as the police. The purpose of this study is to analyze and explain the factors that can increase work engagement in police membership. This study is a systematic literature review with samples in the form of secondary data from journals searched through Google Scholar, Publish or Perish, Academia.edu, and PubMed Central. The main keywords and focus of this study are "Work Engagement" AND "Members of the Police Force". The questions in this study were made using the PICOS (Population, Intervention, Comparation, Outcomes, and Study) framework. The results of the study showed that there were three groups of factors that had an influence on increasing work involvement in police members. These groups of factors are: individual factors, organizational factors, and social factors. Individual factor groups that have the most types of factors compared to other factor groups. In this case, it can be said that individual factor groups have a dominant role in increasing work engagement in police officers.